Adhesive composition and film sheet

The adhesive composition for semiconductor processing tapes addresses the need for antistatic and heat-resistant properties by using a (meth)acrylic polymer-based film sheet with specific monomers and agents, ensuring reliable peeling and minimal contamination in UV and heat processes.

JP2025005745APending Publication Date: 2025-01-17ZACROS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023106068
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Semiconductor processing tapes require improved antistatic performance and heat resistance, especially in processes like fan-out wafer level packages, where conventional UV release adhesives fail to maintain adhesive strength during heating and can damage electronic components.

Method used

An adhesive composition comprising a (meth)acrylic polymer with specific alkyl groups, copolymerizable nitrogen-containing vinyl monomers, and hydroxyl group-containing monomers, combined with a tetrafunctional unsaturated double bond compound, crosslinking agent, silane coupling agent, and antistatic agent, which forms a film sheet with a PEEK base material for enhanced UV peeling and heat resistance.

Benefits of technology

The adhesive composition maintains heat resistance and antistatic performance, allowing easy peeling after UV irradiation and heat processes, preventing adhesive strength increase and component damage, while ensuring minimal surface contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005745000001_ABST
    Figure 2025005745000001_ABST
Patent Text Reader

Abstract

To provide an adhesive composition and a film sheet which can be suitably used as a UV release adhesive for semiconductor processing and have excellent heat resistance as well as antistatic performance.SOLUTION: There is provided an adhesive composition constituting an adhesive layer 11 which comprises a (meth)acrylic polymer having a weight average molecular weight of 1000000 to 3500000 and containing (A) an alkyl (meth)acrylate having an alkyl group having 1 to 18 carbon atoms, (B) a copolymerizable nitrogen-containing vinyl monomer which is a copolymerizable monomer containing no carboxyl group and (C) a copolymerizable monomer containing a hydroxyl group, (D) an acrylate having four or more unsaturated double bonds in the molecule as a tetra- or more functional unsaturated double bond compound, (E) a tri- or more functional aromatic isocyanate compound as a crosslinking agent, (F) a silane coupling agent, (G) an ionic compound having a melting point of 25°C or more as an antistatic agent and (H) a photoinitiator.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition and a film sheet. [Background technology]

[0002] As adhesives used in semiconductor processing tapes, so-called UV-removable adhesives, such as adhesives for dicing tapes, are generally known (see, for example, Patent Document 1). After UV irradiation, the adhesive strength of the UV-removable adhesive decreases to 1 N or less, making it easy to remove. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6713864 Summary of the Invention [Problem to be solved by the invention]

[0004] Today's semiconductor processes are becoming more complex, and the requirements for semiconductor processing tapes are becoming stricter every year. In particular, for semiconductor processing tapes used in processes where ICs are directly mounted on wafers, such as fan-out wafer-level packaging (FO-WLP), heat resistance is also required for reflow processes. Furthermore, to prevent damage to electronic components such as ICs, antistatic properties are sometimes required when the processing tape is peeled off.

[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive composition and a film sheet that can be suitably used as a UV-release pressure-sensitive adhesive for semiconductor processing, and that have excellent heat resistance as well as antistatic performance. [Means for solving the problem]

[0006] A first aspect is a pressure-sensitive adhesive composition comprising a (meth)acrylic polymer, a tetrafunctional or higher unsaturated double bond compound, a crosslinking agent, (F) a silane coupling agent, (G) an antistatic agent, and (H) a photoinitiator, wherein the (meth)acrylic polymer is a copolymer having a weight average molecular weight of 1,000,000 to 3,500,000, which contains (A) one or more alkyl (meth)acrylates having an alkyl group with a carbon number of C1 to C18 and a copolymerizable monomer not containing a carboxyl group, (B) one or more copolymerizable nitrogen-containing vinyl monomers, and (C) one or more copolymerizable monomers containing a hydroxyl group, and the unsaturated double bond is preferably a tetrafunctional or higher unsaturated double bond compound. The (D) copolymerizable compound is one or more selected from acrylates having four or more unsaturated double bonds in the molecule, and the pressure-sensitive adhesive composition contains 0.1 to 10 parts by weight of the (E) tri- or higher functional aromatic isocyanate compound as the crosslinking agent, 0.1 to 3 parts by weight of the (F) silane coupling agent, 0.5 to 30 parts by weight of one or more ionic compounds having a melting point of 25°C or more as the (G) antistatic agent, and 0.1 to 5.0 parts by weight of the (H) photoinitiator, relative to 100 parts by weight of the total of the (A) alkyl (meth)acrylate having a carbon number of C1 to C18 in the alkyl group and the (B) copolymerizable nitrogen-containing vinyl monomer.

[0007] In the second aspect, in the first aspect, a 20 μm thick adhesive layer formed from the adhesive composition by heat drying treatment is laminated on a 27 μm thick PEEK substrate, and the adhesive film has a 90° peel adhesion strength of 1 N / 25 mm or more against a PBO-treated silicon wafer, and the silicon wafer is then irradiated with UV light at a rate of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp, and heated at 240° C. for 5 minutes and further heated at 165° C. for 2.5 hr. The adhesive strength after the test is 0.5 N / 25 mm or less, and the surface resistivity of the surface of the adhesive layer after peeling from the silicon wafer is 1.0×10 +10 It has an adhesive strength of Ω / □ or less, and when tested in the same manner as the silicon wafer, it has an adhesive strength of 0.5 N / 25 mm or more to stainless steel (BA treated), and does not contaminate the surface of the silicon wafer after peeling.

[0008] The third aspect is the first or second aspect, wherein the (meth)acrylic polymer comprises 70 to 95 parts by weight of at least one of the (A) alkyl (meth)acrylates having a carbon number of C1 to C18 in the alkyl group, the (A) containing 40 parts by weight or more of n-butyl acrylate, and 100 parts by weight of the (B) copolymerizable nitrogen-containing vinyl monomer, the total of 5 to 30 parts by weight of a nitrogen-containing vinyl monomer not containing a hydroxyl group, and one or more of the (C) copolymerizable monomers containing a hydroxyl group.

[0009] A fourth aspect is any one of the first to third aspects, wherein the (meth)acrylic polymer contains, as the (C) hydroxyl group-containing copolymerizable monomer, one or more selected from a hydroxyl group-containing (meth)acrylate and a hydroxyl group-containing (meth)acrylamide in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the total of the (A) alkyl (meth)acrylate having a carbon number of C1 to C18 in the alkyl group and the (B) copolymerizable nitrogen-containing vinyl monomer.

[0010] A fifth aspect is any one of the first to fourth aspects, wherein the ionic compound having a melting point of 25° C. or more as the (G) antistatic agent is (G-1) an ammonium-based ionic compound having a fluoro group-containing anion, the fluoro group-containing anion being one selected from the group consisting of pentafluorobenzenesulfonate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and triflate; or (G-2) an ionic compound consisting of a borate anion having a pentafluorophenyl group (CF group) and a cation, the cation being one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyridinium ... (G-3) An ionic compound consisting of a nonafluorobutanesulfonate anion and a cation, the cation containing 0.5 to 30 parts by weight of one or more selected from the group of ionic compounds consisting of pyrrolidinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium.

[0011] A sixth aspect is any one of the first to fifth aspects, wherein the (C) hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.

[0012] In a seventh aspect, in any one of the first to sixth aspects, the pressure-sensitive adhesive composition contains 5 to 30 parts by weight of at least one acrylate compound selected from the group consisting of pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol polyacrylate, and polypentaerythritol polyacrylate as the (D) acrylate having four or more unsaturated double bonds in the molecule, per 100 parts by weight of the total of the (A) alkyl (meth)acrylate having a carbon number of C1 to C18 in the alkyl group and the (B) copolymerizable nitrogen-containing vinyl monomer.

[0013] An eighth aspect is any one of the first to seventh aspects, wherein the (E) tri- or higher functional aromatic isocyanate compound is one or more selected from an adduct of tolylene diisocyanate and an adduct of xylylene diisocyanate. A ninth aspect is any one of the first to eighth aspects, wherein the (F) silane coupling agent has, as an organic functional group, at least one selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, an amino group, and a polyether group.

[0014] A tenth aspect is a film sheet having a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition according to any one of the first to ninth aspects. An eleventh aspect is the tenth aspect, characterized in that the substrate of the pressure-sensitive adhesive layer is a heat-resistant substrate having a thickness of 25 μm or more. A twelfth aspect is characterized in that, in the eleventh aspect, the heat-resistant substrate is a heat-resistant substrate having a thickness of 25 μm or more selected from a polyimide-based film, PEEK, PEN, a polyamide-based film, and a polystyrene-based film.

[0015] A thirteenth aspect is any one of the tenth to twelfth aspects, characterized in that the composition is used in a semiconductor processing step. A fourteenth aspect is the thirteenth aspect, characterized in that the semiconductor processing step is a wafer level packaging step. Effect of the Invention

[0016] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition and a film sheet which can be suitably used as a UV-release pressure-sensitive adhesive for semiconductor processing and which have excellent heat resistance as well as antistatic properties.

[0017] The adhesive composition of the present invention can be used as an adhesive that maintains the performance of conventional UV-removable adhesives while also retaining heat resistance, and can be easily peeled off even after processes that require heat resistance. Conventional UV-removable adhesives could not be adapted to new manufacturing processes because their adhesive strength increased significantly during the heating process after UV irradiation, but the present invention uses an adhesive composition containing a (meth)acrylic polymer of a specific composition and other compounds, making it possible to achieve both UV-removable performance and heat resistance. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a cross-sectional view showing an example in which a film sheet is attached to an adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, the present invention will be described based on preferred embodiments.

[0020] The pressure-sensitive adhesive composition of the embodiment is a pressure-sensitive adhesive composition containing a (meth)acrylic polymer, a tetra- or higher functional unsaturated double bond compound, a crosslinking agent, (F) a silane coupling agent, (G) an antistatic agent, and (H) a photoinitiator, in which the (meth)acrylic polymer contains (A) one or more alkyl (meth)acrylates having an alkyl group with a carbon number of C1 to C18, (B) one or more copolymerizable nitrogen-containing vinyl monomers which are copolymerizable monomers not containing a carboxyl group, and (C) one or more copolymerizable monomers containing a hydroxyl group.

[0021] The (meth)acrylic polymer may be a copolymer of (A) one or more alkyl (meth)acrylates having an alkyl group with a carbon number of C1 to C18, (B) one or more copolymerizable nitrogen-containing vinyl monomers, and (C) one or more copolymerizable monomers containing a hydroxyl group, or may further contain other monomers. The (meth)acrylic polymer is preferably prepared by copolymerizing only copolymerizable monomers not containing a carboxyl group.

[0022] (A) an alkyl (meth)acrylate having an alkyl group with a carbon number of C1 to C18 and (B) a copolymerizable nitrogen-containing vinyl monomer are monomers that do not contain a hydroxyl group or a carboxyl group. In the following description, the total ratio of these may be referred to as "100 parts by weight of the total of (A) and (B)."

[0023] (A) Alkyl (meth)acrylate having an alkyl group with a carbon number of C1 to C18 is not particularly limited and may be appropriately selected. Examples of the alkyl group of the alkyl (meth)acrylate monomer include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, s-butyl, t-butyl, pentyl, hexyl, heptyl, n-octyl, isooctyl, 2-ethylhexyl, n-nonyl, isononyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, myristyl, stearyl, isomyristyl, isostearyl, cyclopentyl, and cyclohexyl.

[0024] In this specification, (meth)acrylate may be either acrylate and / or methacrylate. For example, when the alkyl group is n-butyl, n-butyl(meth)acrylate may be either n-butylacrylate and / or n-butylmethacrylate. The alkyl group of the alkyl(meth)acrylate monomer may be either acyclic (straight-chain or branched) or cyclic.

[0025] The alkyl (meth)acrylate (A) having an alkyl group with a carbon number of C1 to C18 to be copolymerized in the (meth)acrylic polymer may be one type or two or more types. The (meth)acrylic polymer preferably contains 70 to 95 parts by weight of at least one type of alkyl (meth)acrylate (A) having an alkyl group with a carbon number of C1 to C18 in total, out of 100 parts by weight of (A) and (B).

[0026] The (meth)acrylic polymer preferably contains 40 parts by weight or more of n-butyl acrylate out of 100 parts by weight in total of (A) and (B). The ratio of n-butyl acrylate may be 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight, 95 parts by weight, etc. In the (meth)acrylic polymer, the alkyl (meth)acrylate (A) having a carbon number of C1 to C18 in the alkyl group may be n-butyl acrylate alone, or n-butyl acrylate may be used in combination with another alkyl (meth)acrylate.

[0027] In the (meth)acrylic polymer, the (B) copolymerizable nitrogen-containing vinyl monomer is a copolymerizable monomer that does not contain a carboxyl group and is different from the (C) copolymerizable monomer that contains a hydroxyl group. The (B) copolymerizable nitrogen-containing vinyl monomer is preferably a monofunctional unsaturated double bond compound.

[0028] (B) The copolymerizable nitrogen-containing vinyl monomer is not particularly limited, but examples thereof include N-vinyl-substituted lactams, N-vinyl-substituted cyclic amines, N-(meth)acryloyl-substituted cyclic amines, acrylic monomers containing an N,N-dialkyl-substituted amino group, acrylic monomers containing an N,N-dialkyl-substituted amide group, etc. In this specification, (meth)acryloyl may be either acryloyl and / or methacryloyl.

[0029] Examples of N-vinyl substituted lactams include N-vinylpyrrolidone, methylvinylpyrrolidone, and N-vinylcaprolactam. Examples of N-vinyl substituted cyclic amines include N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, and N-vinylmorpholine.

[0030] Examples of the N-(meth)acryloyl-substituted cyclic amines include N-(meth)acryloylmorpholine, N-(meth)acryloylpiperazine, N-(meth)acryloylaziridine, N-(meth)acryloylpyrrolidine, and N-(meth)acryloylpiperidine.

[0031] Examples of acrylic monomers containing an N,N-dialkyl-substituted amino group include dialkylamino-substituted alkyl (meth)acrylates and dialkylamino-substituted alkyl (meth)acrylamides. Examples of acrylic monomers containing an N,N-dialkyl-substituted amide group include N,N-dialkyl-substituted (meth)acrylamides. In this specification, (meth)acrylamides may be either acrylamides and / or methacrylamides.

[0032] Examples of dialkylamino-substituted alkyl (meth)acrylates include N-ethyl-N-methylaminoethyl (meth)acrylate, N-methyl-N-propylaminoethyl (meth)acrylate, N-methyl-N-isopropylaminoethyl (meth)acrylate, N,N-dimethylaminomethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminobutyl (meth)acrylate, N,N-dipropylaminoethyl (meth)acrylate, and N,N-dibutylaminoethyl (meth)acrylate.

[0033] Examples of dialkylamino-substituted alkyl(meth)acrylamides include N-ethyl-N-methylaminopropyl(meth)acrylamide, N-methyl-N-propylaminopropyl(meth)acrylamide, N-methyl-N-isopropylaminopropyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, N,N-dipropylaminopropyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylamide, N,N-diethylaminoethyl(meth)acrylamide, etc. The dialkylamino-substituted alkyl group may be an N-substituent of the (meth)acrylamide compound.

[0034] Examples of N,N-dialkyl substituted (meth)acrylamides include N-ethyl-N-methyl(meth)acrylamide, N-methyl-N-propyl(meth)acrylamide, N-methyl-N-isopropyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-dibutyl(meth)acrylamide.

[0035] The (B) copolymerizable nitrogen-containing vinyl monomer to be copolymerized in the (meth)acrylic polymer may be one type or two or more types. The (meth)acrylic polymer preferably contains at least one or more types of copolymerizable nitrogen-containing vinyl monomer (B) in a ratio of 5 to 30 parts by weight per 100 parts by weight of the total of (A) and (B).

[0036] In the (meth)acrylic polymer, the copolymerizable monomer (C) containing a hydroxyl group may be a hydroxyl group-containing (meth)acrylate, a hydroxyl group-containing (meth)acrylamide, etc. The copolymerizable monomer (C) containing a hydroxyl group is a monomer that does not contain a carboxyl group. The copolymerizable monomer (C) containing a hydroxyl group is preferably a monofunctional unsaturated double bond compound.

[0037] Examples of the hydroxyl group-containing (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate. Examples of hydroxyl group-containing (meth)acrylamides include N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.

[0038] It is preferable that the (C) hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.

[0039] The (C) hydroxyl group-containing copolymerizable monomer to be copolymerized in the (meth)acrylic polymer may be one type or two or more types. The (meth)acrylic polymer preferably contains at least one or more hydroxyl group-containing copolymerizable monomers (C) in a total amount of 0.1 to 5 parts by weight per 100 parts by weight of (A) and (B) in total.

[0040] The copolymerizable monomer containing a hydroxyl group (C) can react with the isocyanate compound of the crosslinking agent, similarly to the monomer containing a carboxyl group. Therefore, by using the copolymerizable monomer containing a hydroxyl group (C) without using the monomer containing a carboxyl group, it is possible to improve the adhesive strength of the pressure-sensitive adhesive layer and reduce the corrosiveness. The acid value of the (meth)acrylic polymer may be 0.1 or less.

[0041] The polymerization method for the copolymer used as the (meth)acrylic polymer is not particularly limited, and any known polymerization method such as solution polymerization, emulsion polymerization, etc. can be used as appropriate. The (meth)acrylic polymer preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylate monomer or a (meth)acrylamide monomer.

[0042] The weight average molecular weight of the (meth)acrylic polymer is preferably from 1,000,000 to 3,500,000, and may be 1,500,000 or more.

[0043] The pressure-sensitive adhesive composition of the embodiment contains a tetrafunctional or higher unsaturated double bond compound together with the (meth)acrylic polymer. The unsaturated double bond contained in the unsaturated double bond compound is preferably a carbon-carbon unsaturated double bond that does not constitute an aromatic ring. The unsaturated double bond may be contained in a (meth)acryloyl group of (meth)acrylate, (meth)acrylamide, etc., or may be a vinyl group, an allyl group, etc.

[0044] The unsaturated double bond compound is preferably one or more selected from (D) acrylates having four or more unsaturated double bonds in the molecule. Examples of the acrylates having four or more unsaturated double bonds in the molecule include acrylate compounds derived from polyol compounds having four or more hydroxyl groups in the molecule.

[0045] Examples of the polyol compound include pentaerythritol, dipentaerythritol, polypentaerythritol, ditrimethylolpropane, polytrimethylolpropane, etc. (D) An acrylate having four or more unsaturated double bonds in the molecule corresponds to a compound in which all or a part of the hydroxyl groups contained in the polyol compound are converted into four or more acrylates.

[0046] The pressure-sensitive adhesive composition preferably contains 1 to 50 parts by weight, more preferably 5 to 30 parts by weight, of (D) an acrylate having four or more unsaturated double bonds in the molecule, relative to 100 parts by weight of the total of (A) and (B).Furthermore, as (D) an acrylate having four or more unsaturated double bonds in the molecule, it is preferable that the pressure-sensitive adhesive composition contains 5 to 30 parts by weight of at least one acrylate compound selected from the group consisting of pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol polyacrylate, and polypentaerythritol polyacrylate.

[0047] The pressure-sensitive adhesive composition preferably contains, as a crosslinking agent, (E) a trifunctional or higher aromatic isocyanate compound. Examples of the aromatic isocyanate compound include compounds derived from tolylene diisocyanate (TDI), xylylene diisocyanate (XDI), diphenylmethane diisocyanate (MDI), etc.

[0048] Examples of the trifunctional or higher isocyanate compound include an adduct of a bifunctional isocyanate compound, a biuret, an isocyanurate, etc. Examples of the adduct include an adduct with a trivalent or higher polyol such as trimethylolpropane (TMP) or glycerin.

[0049] The trifunctional or higher aromatic isocyanate compound (E) is preferably one or more selected from the group consisting of an adduct of tolylene diisocyanate and an adduct of xylylene diisocyanate. The pressure-sensitive adhesive composition preferably contains the trifunctional or higher aromatic isocyanate compound (E) in an amount of 0.1 to 10 parts by weight per 100 parts by weight of the total of (A) and (B).

[0050] The pressure-sensitive adhesive composition contains (F) a silane coupling agent. (F) The silane coupling agent preferably has at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, an amino group, and a polyether group. In addition, alkoxy oligomers (silicone alkoxy oligomers) containing these organic functional groups and oligomerized can also be suitably used as (F) the silane coupling agent.

[0051] Examples of silane coupling agents having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 5,6-epoxyhexyltrimethoxysilane, and 5,6-epoxyhexylmethyldimethoxysilane.

[0052] Examples of silane coupling agents having a (meth)acryloxy group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, and 3-(meth)acryloxypropyldimethylmethoxysilane.

[0053] Examples of the silane coupling agent having a mercapto group include 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, and 3-mercaptopropyltriethoxysilane.

[0054] Examples of silane coupling agents having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-(methylamino)propyltrimethoxysilane, and 3-(methylamino)propyltriethoxysilane.

[0055] Examples of the silane coupling agent having a polyether group include those represented by the general formula: R 1 -(OR 2 ) n -Si(OR 3 ) 3 is a perfluoropolyether group-containing silane coupling agent represented by the formula: 1 is a perfluoroalkyl group such as C3F7. n R 2 may be the same or different, and are perfluoroalkylene groups such as CF, CF, and CF, or alkylene groups such as CH, CH, and CH. 3 is an alkyl group such as a methyl group or an ethyl group, and n is an integer of 1 or more.

[0056] The pressure-sensitive adhesive composition preferably contains 0.1 to 3 parts by weight of the silane coupling agent (F) per 100 parts by weight of the total of (A) and (B).

[0057] The pressure-sensitive adhesive composition contains an antistatic agent (G). The pressure-sensitive adhesive composition preferably contains 0.5 to 30 parts by weight of the antistatic agent (G) per 100 parts by weight of the total of (A) and (B).

[0058] The pressure-sensitive adhesive composition preferably contains, as the (G) antistatic agent, one or more ionic compounds having a melting point of 25° C. or higher. As the (G) antistatic agent, an ionic compound having a melting point of 25° C. or higher can be selected from ionic compounds having a cation and an anion by selecting the cation and / or the anion. When the melting point of the (G) antistatic agent is 25° C. or higher, the heat resistance of the antistatic agent can be maintained, and bleeding out onto the surface of the pressure-sensitive adhesive layer and contamination of the adherend can be prevented.

[0059] The cation of the (G) antistatic agent may be one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium. These cations may have one or more substituents, except when the cation is lithium. The substituent of the cation may be an organic group such as an alkyl group.

[0060] (G) The anion of the antistatic agent may be an inorganic or organic fluoro group-containing anion. Here, the fluoro group means a fluorine atom bonded to another atom constituting the anion. An example of the inorganic fluoro group-containing anion is PF6. - , AsF6 - , SbF6 - , BF4 - , AlF4 - , (FSO2)2N - , FSO3 - , etc. Examples of organic fluoro group-containing anions include fluoro group-containing sulfonate anions (RSO3 - ), fluoro-containing carboxylate anion (RCOO - ), alkoxide or phenoxide anion containing a fluoro group (RO - ), fluoro-containing organic imide anion (RN - ), fluoro-containing methides (R - ) anion, fluoro-containing organic borate (R4B -) anion, and the like, in which at least one of R is an anion having a fluoro group-containing organic group.

[0061] (G) The organic group of R in the anion of the antistatic agent may be one or more of an alkyl group, an alkoxy group, an aromatic group (an aryl group, an aralkyl group, etc.), an alkylcarbonyl group, an aromatic carbonyl group, an alkylsulfonyl group, an aromatic sulfonyl group, etc. When the anion has two or more R, the two or more R may have a bond between them to form a ring.

[0062] The ionic compound having a melting point of 25°C or higher as the (G) antistatic agent preferably contains 0.5 to 30 parts by weight of one or more types selected from the group consisting of the following ionic compounds (G-1) to (G-3) per 100 parts by weight of the total of (A) and (B).

[0063] (G-1) The ammonium-based ionic compound having a fluoro group-containing anion includes an ionic compound in which the fluoro group-containing anion is one selected from the group consisting of pentafluorobenzenesulfonate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and triflate. The ammonium-based ionic compound has ammonium as a cation. The ammonium substituent may be a substituent that does not contain a fluoro group or a substituent that contains a fluoro group.

[0064] (G-2) Ionic compounds consisting of a borate anion having a pentafluorophenyl group (C6F5 group) and a cation include ionic compounds in which the cation is one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium. As the borate anion having a C6F5 group, at least one of the four organic groups R may be a C6F5 group, and a specific example is B(C6F5)4. - Examples include:

[0065] (G-3) Examples of ionic compounds consisting of a nonafluorobutanesulfonate anion and a cation include ionic compounds in which the cation is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium.

[0066] The pressure-sensitive adhesive composition contains a photoinitiator (H). The photoinitiator (H) is not particularly limited, but examples thereof include acetophenone-based photoinitiators, benzoin-based photoinitiators, benzophenone-based photoinitiators, and thioxanthone-based photoinitiators.

[0067] Examples of acetophenone-based photoinitiators include acetophenone, p-(tert-butyl)1',1',1'-trichloroacetophenone, chloroacetophenone, 2',2'-diethoxyacetophenone, hydroxylacetophenone, 2,2-dimethoxy-2'-phenylacetophenone, 2-aminoacetophenone, dialkylaminoacetophenone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone, and the like.

[0068] Benzoin-based photoinitiators include benzil, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-2-methylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, benzil dimethyl ketal, 2,2-dimethoxy-1,2-diphenylethan-1-one, and the like.

[0069] Benzophenone-based photoinitiators include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, methyl-o-benzoylbenzoate, 4-phenylbenzophenone, hydroxylbenzophenone, hydroxylpropylbenzophenone, acrylbenzophenone, and 4,4'-bis(dimethylamino)benzophenone.

[0070] Examples of the thioxanthone-based photoinitiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, diethylthioxanthone, and dimethylthioxanthone.

[0071] Other photoinitiators include α-acyloxime esters, benzyl-(o-ethoxycarbonyl)-α-monoxime, acylphosphine oxides, phenylglyoxylic acid esters, 3-ketocoumarin, 2-ethylanthraquinone, camphorquinone, tetramethylthiuram sulfide, azobisisobutyronitrile, benzoyl peroxide, dialkyl peroxide, and tert-butyl peroxypivalate.

[0072] The pressure-sensitive adhesive composition preferably contains 0.1 to 5.0 parts by weight of the photoinitiator (H) relative to 100 parts by weight in total of (A) and (B).

[0073] In addition to the above-mentioned examples, the pressure-sensitive adhesive composition of the embodiment may appropriately contain, as optional components, known additives such as antioxidants, surfactants, curing accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, curing retarders, processing aids, antiaging agents, and antistatic agents. These may be used alone or in combination of two or more kinds.

[0074] The adhesive film formed by the heat drying treatment of the adhesive composition of the embodiment preferably has a 90° peel adhesion strength of 1N / 25mm or more against a PBO-treated silicon wafer. Here, PEEK is polyether ether ketone resin, and PBO treatment is polybenzoxazole. The adhesive film for adhesive strength testing may be, for example, a 20μm thick adhesive layer laminated on a 27μm thick PEEK substrate.

[0075] Furthermore, the adhesive film formed by the heat drying treatment preferably has a 90° peel adhesion strength of 0.5 N / 25 mm or less against a PBO-treated silicon wafer (before the heat treatment described below, which is performed by heating at 240°C for 5 minutes and then at 165°C for 2.5 hours) after UV irradiation of a 30.48 cm (12 inch) diameter adherend (silicon wafer) at a rate of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp after the heat drying treatment. The adhesive strength is more preferably 0.3 N / 25 mm or less.

[0076] Furthermore, the adhesive film formed by the heat drying treatment is irradiated with UV light from a metal halide lamp or a 365 nm wavelength LED-UV lamp at a rate of 3000 mJ on an adherend (silicon wafer) with a diameter of 30.48 cm (12 inches), then heated at 240°C for 5 minutes and further heated at 165°C for 2.5 hours. After the test, the 90° peel adhesion strength against a PBO-treated silicon wafer is preferably 0.5 N / 25 mm or less. The adhesive strength is more preferably 0.3 N / 25 mm or less.

[0077] Similarly, the adhesive film formed by the heat drying treatment is irradiated with UV light at a rate of 3000 mJ on a 30.48 cm (12 inch) diameter adherend (BA treated stainless steel) using a metal halide lamp or a 365 nm wavelength LED-UV lamp after the heat drying treatment, then heated at 240°C for 5 minutes and further heated at 165°C for 2.5 hours. After the test, the 90° peel adhesion strength against stainless steel (BA treated) is preferably 0.5 N / 25 mm or more. Here, BA treatment refers to bright annealing treatment.

[0078] The surface resistivity of the adhesive layer after peeling from the silicon wafer is 1.0×10 +10 It is preferable that the resistivity is Ω / □ or less. This makes it possible to suppress the peeling electrification of the adhesive film and the adherend. The silicon wafer used for measuring the surface resistivity may be the same as the adherend (PBO-treated silicon wafer) used for measuring the adhesive strength.

[0079] It is preferable that the pressure-sensitive adhesive film does not contaminate the surface of the silicon wafer after peeling, thereby making it possible to prevent surface contamination of the adherend, such as the silicon wafer.

[0080] The adhesive layer made of the adhesive composition of the embodiment can be used for a film sheet. Fig. 1 shows an example in which an adhesive layer 11 of a film sheet 10 is attached to an adherend 20. The film sheet 10 preferably has the adhesive layer 11 on one surface of a substrate 12.

[0081] The substrate 12 is preferably a heat-resistant substrate having a thickness of 25 μm or more. The heat-resistant substrate is preferably a heat-resistant substrate having a thickness of 25 μm or more selected from a polyimide film, polyether ether ketone (PEEK), polyethylene naphthalate (PEN), a polyamide film, and a polystyrene film.

[0082] It is preferable to select a material with high heat resistance so as to meet the requirements of the semiconductor processing process as the substrate 12. Examples of polyamide-based and polystyrene-based films include aromatic polyamide, syndiotactic polystyrene (SPS), etc., which have higher heat resistance than general-purpose resins (nylon and general-purpose polystyrene).

[0083] The film sheet 10 can be used in semiconductor processing steps such as a wafer level package (WLP) step. The pressure-sensitive adhesive layer 11 is preferably attached to an adherend 20 in a state in which the (meth)acrylic polymer contained in the pressure-sensitive adhesive composition is crosslinked using (E) a trifunctional or higher aromatic isocyanate compound as a crosslinking agent.

[0084] Furthermore, it is preferable that the adhesive strength of the film sheet 10 to a silicon wafer is reduced by ultraviolet (UV) irradiation, and that the adhesive strength to stainless steel is maintained at a predetermined level or higher even after ultraviolet (UV) irradiation.

[0085] Before being attached to the adherend 20, the film sheet 10 may use a release film (separator) to protect the adhesive surface of the adhesive layer 11. As the release film, a resin film such as a polyester film may be used. The release film may be one that has been treated with a release agent, a coating agent, an antifouling treatment, or an antistatic treatment.

[0086] Although the present invention has been described above based on the preferred embodiments, the present invention is not limited to the above-mentioned embodiments, and various modifications can be made without departing from the spirit of the present invention. Modifications include addition, substitution, omission, and other changes to components in each embodiment. EXAMPLES

[0087] The present invention will now be described in detail with reference to examples.

[0088] <Production of acrylic polymer> Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, the monomers shown in Table 1 were added so that the total of (A) and (B) was 100 parts by weight, and 60 parts by weight of a solvent (ethyl acetate) was added. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution. The weight average molecular weight (Mw) of the acrylic polymer is shown in Table 1.

[0089] [Table 1]

[0090] The meanings of the abbreviations (compound names, etc.) used in Table 1 are as follows. The numerical values ​​following these abbreviations in Table 1 indicate parts by weight based on 100 parts by weight of the total of (A) and (B).

[0091] In Table 1, n-butyl acrylate (BA), ethyl acrylate (EA), 2-ethylhexyl acrylate (2EHA), methyl acrylate (MA), isooctyl acrylate (IOA), isobutyl acrylate (IBA), and n-butyl methacrylate (BMA) were used in group (A).

[0092] In addition, N-vinylpyrrolidone (NVP), N,N-diethylacrylamide (DEAA), N,N-dimethylacrylamide (DMAA), N,N-diisopropylacrylamide (DIPAA), and N-[3-(dimethylamino)propyl]methacrylamide (DMAPMA) were used in group (B).

[0093] In addition, 8-hydroxyoctyl acrylate (8HOA), 6-hydroxyhexyl acrylate (6HHA), 4-hydroxybutyl acrylate (4HBA), 2-hydroxyethyl acrylate (HEA), N-hydroxymethylacrylamide (HMAA), and N-hydroxyethylacrylamide (HEAA) were used in group (C).

[0094] The (X) group is a monomer containing a carboxyl group, and in Comparative Example 4, acrylic acid (AAc) was used.

[0095] <Production of Pressure-Sensitive Adhesive Composition and Pressure-Sensitive Adhesive Layer> The additives shown in Table 2 were added to the above-mentioned acrylic polymer solution and mixed by stirring to obtain a pressure-sensitive adhesive composition. This pressure-sensitive adhesive composition was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then the solvent was removed by drying at 90°C. After that, a pressure-sensitive adhesive layer was obtained by aging for 7 days in an atmosphere of 23°C and 50% RH. For the pressure-sensitive adhesive film for adhesive strength testing, a 20 μm-thick pressure-sensitive adhesive layer may be laminated onto a 27 μm-thick PEEK substrate.

[0096] [Table 2]

[0097] The meanings of the abbreviations (compound names, etc.) used in Table 2 are as follows. The numerical values ​​following these abbreviations in Table 2 indicate parts by weight relative to 100 parts by weight of the total of (A) and (B).

[0098] In Table 2, the (D) group includes tetrafunctional pentaerythritol tetraacrylate (D-1), hexafunctional or higher polypentaerythritol polyacrylate (D-2), tetrafunctional ditrimethylolpropane tetraacrylate (D-3), hexafunctional dipentaerythritol hexaacrylate (D-4), difunctional 1,6-hexanediol diacrylate (D-5), and trifunctional pentaerythritol triacrylate (D-6).

[0099] As group (E), Takenate (registered trademark) D-101, Takenate (registered trademark) D-110N, and Coronate (registered trademark) HL were used. "D-101" is an adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP), "D-110N" is an adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP), and "HL" is an adduct of hexamethylene diisocyanate (HDI).

[0100] In addition, for group (F), a silane coupling agent having an epoxy group (product name: X-24-9590) was used as "F-1", a silane coupling agent having a mercapto group (product name: X-12-1154) was used as "F-2", and a silane coupling agent having an acryloxy group (product name: KBM-503) was used as "F-3".

[0101] The (G) group includes tetrabutylammonium triflate (melting point 113°C) as "G-1-1", methyltri-n-butylammonium bis(trifluoromethanesulfonyl)imide (melting point 27°C) as "G-1-2", trimethylhexylammonium bis(trifluoromethanesulfonyl)imide (melting point 27°C) as "G-1-3", 4-methyl-1-hexylpyridinium bis(trifluoromethanesulfonyl)imide (melting point less than 25°C) as "G-1-4", triphenylmethylium tetrakis(pentafluorophenyl)borate (melting point 183°C) as "G-2-1", (methoxymethyl)triphenylphosphonium tetrakis(pentafluorophenyl)borate (melting point 149°C) as "G-2-2", and 1-ethyl-3-methylimidazolium as "G-2-3". As "G-3-1", lithium nonafluorobutanesulfonate (melting point 370°C) was used, as "G-3-2", 4-methyl-1-octylpyridinium nonafluorobutanesulfonate (melting point 62°C) was used, and as "G-3-3", 3-methyl-1-octylpyridinium nonafluorobutanesulfonate (melting point 41°C) was used.

[0102] In addition, as group (H), the alkylphenone-based OMNIRAD (registered trademark) 184 was used as "H-1", the alkylphenone-based OMNIRAD (registered trademark) 369 was used as "H-2", the oxime ester-based IRGACURE (registered trademark) OXE01 was used as "H-3", and the acylphosphine oxide-based OMNIRAD (registered trademark) TPO was used as "H-4".

[0103] <Manufacturing of film sheets> A film sheet was produced by transferring the adhesive layer formed on the release film onto the heat-resistant substrate shown in Table 3. The materials of the heat-resistant substrate were polyether ether ketone (PEEK), polyethylene naphthalate (PEN), polyamide (PA)-based film, and polystyrene (PS)-based film.

[0104] The initial adhesive strength shown in Table 3 was measured as the 90° peel adhesive strength after the adhesive layer of the film sheet was attached to the PBO-treated wafer. The adhesive strength in Table 3 is indicated as "initial".

[0105] The adhesive strength after UV irradiation shown in Table 3 was measured as 90° peel adhesive strength after the adhesive layer of the film sheet was laminated to the PBO-treated wafer, and then UV irradiation was performed at a rate of 3000 mJ on an adherend with a diameter of 30.48 cm (12 inches) using a metal halide lamp or a 365 nm wavelength LED-UV lamp. The adhesive strength in Table 3 is indicated as "UV".

[0106] The adhesive strength after UV irradiation and heating shown in Table 3 was measured by laminating the adhesive layer of the film sheet to an adherend selected from PBO-treated wafers or BA-treated stainless steel (SUS), irradiating UV light at a rate of 3000 mJ per adherend with a diameter of 30.48 cm (12 inches) using a metal halide lamp or a 365 nm wavelength LED-UV lamp, heating at 240°C for 5 minutes, and then heating at 165°C for 2.5 hours, after which the 90° peel adhesive strength was measured. The adhesive strength in Table 3 is shown as "UV + heating".

[0107] [Table 3]

[0108] The reworkability shown in Table 3 was rated as good (○) when the adhesive strength of the film sheet after UV irradiation and heating was less than 0.3 N / 25 mm, fair (△) when it was 0.3 N / 25 mm or more but less than 3 N / 25 mm, and poor (×) when it was 3 N / 25 mm or more.

[0109] The surface resistivity shown in Table 3 was measured by applying a resistivity meter to the adhesive layer after peeling it off from the adherend (PBO-treated wafer). The measurement results are expressed as "m×10 +n " is expressed as "mE+n" (where m and n are positive real numbers).

[0110] The stain resistance shown in Table 3 was measured by measuring the adhesive strength of the film sheet after UV irradiation and heating, and then visually checking whether the adhesive components had migrated to the surface of the adherend (PBO-treated wafer) to make sure it was not stained. If there was no staining on the adherend at all, it was rated as good (○), if there was light staining on part or the entire adherend, it was rated as fair (△), and if there was staining on the entire surface, it was rated as poor (×).

[0111] In the film sheets of Examples 1 to 9, (1) the initial adhesive strength to the PBO-treated wafer was 1 N / 25 mm or more, (2) the adhesive strength to the PBO-treated wafer after UV irradiation was 0.3 N / 25 mm or less, (3) the adhesive strength to the PBO-treated wafer after UV irradiation and heating was 0.5 N / 25 mm or less, and (4) the adhesive strength to the BA-treated SUS after UV irradiation and heating was 0.5 N / 25 mm or more. Furthermore, the film sheets of Examples 1 to 9 had excellent antistatic performance and contamination resistance.

[0112] None of the film sheets of Comparative Examples 1 to 9 satisfied all of the above requirements (1), (3) and (4). Furthermore, the film sheets of Comparative Examples 1 to 9 were also poor in antistatic performance or stain resistance.

[0113] In Comparative Example 1, the unsaturated double bond compound was a difunctional acrylate, and the pressure-sensitive adhesive composition did not contain an antistatic agent (G). In Comparative Example 2, the (meth)acrylic polymer had Mw of 480,000, and the pressure-sensitive adhesive composition did not contain the (G) antistatic agent. In Comparative Example 3, the (meth)acrylic polymer was not copolymerized with the copolymerizable nitrogen-containing vinyl monomer (B), and the melting point of the antistatic agent (G) was low. In Comparative Example 4, the (meth)acrylic polymer was not copolymerized with the hydroxyl group-containing copolymerizable monomer (C), and the pressure-sensitive adhesive composition did not contain the antistatic agent (G). In Comparative Example 5, the pressure-sensitive adhesive composition does not contain the silane coupling agent (F), and the melting point of the antistatic agent (G) is low. In Comparative Example 6, the unsaturated double bond compound was a trifunctional acrylate, and the pressure-sensitive adhesive composition did not contain the (G) antistatic agent. In Comparative Example 7, the crosslinking agent is an aliphatic isocyanate compound, and the proportion of the (G) antistatic agent is too small. In Comparative Example 8, the pressure-sensitive adhesive composition did not contain the (G) antistatic agent and the (H) photoinitiator. In Comparative Example 9, the pressure-sensitive adhesive composition did not contain the (G) antistatic agent. [Explanation of symbols]

[0114] 10...film sheet, 11...adhesive layer, 12...substrate, 20...adherend.

Claims

1. A pressure-sensitive adhesive composition comprising a (meth)acrylic polymer, a tetrafunctional or higher unsaturated double bond compound, a crosslinking agent, (F) a silane coupling agent, (G) an antistatic agent, and (H) a photoinitiator, the (meth)acrylic polymer is a copolymer having a weight average molecular weight of 1,000,000 to 3,500,000, which contains (A) one or more alkyl (meth)acrylates having an alkyl group with a carbon number of C1 to C18 and a copolymerizable monomer not containing a carboxyl group, (B) one or more copolymerizable nitrogen-containing vinyl monomers, and (C) one or more copolymerizable monomers containing a hydroxyl group; The unsaturated double bond compound is at least one selected from (D) acrylates having four or more unsaturated double bonds in the molecule, The pressure-sensitive adhesive composition comprises With respect to 100 parts by weight of the total of (A) the alkyl (meth)acrylate having an alkyl group with a carbon number of C1 to C18 and (B) the copolymerizable nitrogen-containing vinyl monomer, As the crosslinking agent, (E) 0.1 to 10 parts by weight of a trifunctional or higher aromatic isocyanate compound, 0.1 to 3 parts by weight of the (F) silane coupling agent, The (G) antistatic agent comprises 0.5 to 30 parts by weight of one or more ionic compounds having a melting point of 25° C. or higher, A pressure-sensitive adhesive composition comprising the photoinitiator (H) in an amount of 0.1 to 5.0 parts by weight.

2. an adhesive film obtained by laminating a 20 μm thick adhesive layer formed from the adhesive composition by heat drying treatment on a 27 μm thick PEEK substrate has a 90° peel adhesion strength to a PBO-treated silicon wafer of 1 N / 25 mm or more, and the adhesive film has an adhesive strength of 0.5 N / 25 mm or less after a test in which the silicon wafer having a diameter of 30.48 cm (12 inches) is irradiated with UV light at a rate of 3000 mJ using a metal halide lamp or a 365 nm wavelength LED-UV lamp, and then heated at 240° C. for 5 minutes and further heated at 165° C. for 2.5 hours; The surface resistivity of the surface of the adhesive layer after peeling from the silicon wafer is 1.0×10 +10 Ω / □ or less, The adhesive strength to stainless steel (BA treatment) when tested in the same manner as the silicon wafer is 0.5 N / 25 mm or more.

2. The pressure-sensitive adhesive composition according to claim 1, which does not contaminate the surface of the silicon wafer after peeling.

3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the (meth)acrylic polymer comprises 100 parts by weight of a total of 70 to 95 parts by weight of at least one of the (A) alkyl (meth)acrylates having an alkyl group with a carbon number of C1 to C18, the (A) containing 40 parts by weight or more of n-butyl acrylate, and 5 to 30 parts by weight of a nitrogen-containing vinyl monomer not containing a hydroxyl group as the (B) copolymerizable nitrogen-containing vinyl monomer, and one or more of the (C) copolymerizable monomers containing a hydroxyl group.

4. 3. The pressure-sensitive adhesive composition according to claim 1 or 2, characterized in that the (meth)acrylic polymer contains, as the (C) hydroxyl group-containing copolymerizable monomer, one or more selected from a hydroxyl group-containing (meth)acrylate and a hydroxyl group-containing (meth)acrylamide in an amount of 0.1 to 5 parts by weight per 100 parts by weight of the total of the (A) alkyl (meth)acrylate having a carbon number of C1 to C18 in the alkyl group and the (B) copolymerizable nitrogen-containing vinyl monomer.

5. The ionic compound having a melting point of 25° C. or higher as the (G) antistatic agent is (G-1) An ammonium-based ionic compound having a fluoro group-containing anion, the fluoro group-containing anion being one selected from the group consisting of pentafluorobenzenesulfonate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, and triflate; (G-2) Pentafluorophenyl group (C 6 F 5 a borate anion having a cation group, the cation being one selected from the group consisting of pyridinium, imidazolium, sulfonium, phosphonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium; The pressure-sensitive adhesive composition according to claim 1 or 2, characterized in that (G-3) is an ionic compound consisting of a nonafluorobutanesulfonate anion and a cation, and the cation is one or more selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium, and contains 0.5 to 30 parts by weight of the ionic compound.

6. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the (C) hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.

7. The pressure-sensitive adhesive composition according to claim 1 or 2, characterized in that it contains 5 to 30 parts by weight of at least one acrylate compound selected from the group consisting of pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol polyacrylate, and polypentaerythritol polyacrylate as the (D) acrylate having four or more unsaturated double bonds in the molecule, relative to a total of 100 parts by weight of the (A) alkyl (meth)acrylate having a carbon number of C1 to C18 in the alkyl group and the (B) copolymerizable nitrogen-containing vinyl monomer.

8. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the tri- or higher functional aromatic isocyanate compound (E) is at least one selected from the group consisting of an adduct of tolylene diisocyanate and an adduct of xylylene diisocyanate.

9. The pressure-sensitive adhesive composition according to claim 1 or 2, characterized in that the (F) silane coupling agent has, as an organic functional group, at least one selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, an amino group, and a polyether group.

10. A film sheet comprising an adhesive layer comprising the adhesive composition according to claim 1 or 2.

11. 11. The film sheet according to claim 10, wherein the base material of the pressure-sensitive adhesive layer is a heat-resistant base material having a thickness of 25 μm or more.

12. 12. The film sheet according to claim 11, wherein the heat-resistant substrate is a heat-resistant substrate having a thickness of 25 μm or more selected from the group consisting of polyimide-based films, PEEK, PEN, polyamide-based films, and polystyrene-based films.

13. 11. The film sheet of claim 10, for use in semiconductor processing.

14. The film sheet according to claim 13, which is used in a wafer level packaging process as the semiconductor processing process.

Citation Information

Patent Citations

  • Semiconductor chip manufacturing method and adhesive tape for temporary wafer fixing

    JP6713864B2